China y México 2012-2018, entre el inicio idílico y la realidad - Cornejo, Romer (El Colegio de México A.C., 2019)
Mexico’s relations with China during the  2012-2018 administration saw no significant change compared to previous governments. Mexico continued its approach of failing to take into account China’s weight in the international community, the characteristics of its political system, or its powerful economic projects. Although the relations between both countries began with the slogan of “resetting,” they were hurt by the failures of Chinese economic projects in Mexico. Diplomatic relations followed their usual course, with meetings between officials at various levels and the signing of interesting cooperation agreements. For its part, China maintained an effective cultural policy to create favorable public opinion among academics, politicians and the media.